A STUDY OF ENTREPRENEURIAL TRAITS OF WOMEN ENTRERPRENEURS IN KANYAKUMARI DISTRICT - S.Neelakandan, Dr. N. Sankara Gomathi, (PalArch's Journal of Archaeology of Egypt / Egyptology, 2021)
Entrepreneurship plays a prominent role in industrial development and the concept has appreciably changed in nature and content over the years. The main aim of the study is to identify the entrepreneurial traits of women entrepreneurs and find out the relationship between entrepreneurial traits of women entrepreneurs and personal factors. The present study is descriptive in nature and uses both quantitative and qualitative data for the analysis with the aim of describing the present scenario of entrepreneurial traits of women entrepreneurs in Kanyakumari district. Apart from this, the present study has defined objectives and framed methodology to fulfill the objectives of the study. The study explains the relationship among the variables, profile variables and how it contributes to the entrepreneurial traits of the women entrepreneurs. The data which are related to entrepreneurial traits among the women entrepreneurs in Kanyakumari district are collected through both primary and secondary data. Primary data has been collected from the women entrepreneurs in district through interview scheduled circulated among the prospective respondents of the study. The primary data have been collected from 200 women entrepreneurs by applying stratified random sampling method.The study has identified the six important entrepreneurial traits for the success of an entrepreneur. The improvement of entrepreneurship qualities among the women entrepreneurs is an important step in the social and economic empowerment of women.